Teriflunomide Does Not Change Dynamics of Nadph Oxidase Activation and Neuronal Dysfunction During Neuroinflammation - Mothes, Ronja; Ulbricht, Carolin; Leben, Ruth; Günther, Robert; Hauser, Anja E.; Radbruch, Helena; Niesner, Raluca (Frontiers in Molecular Biosciences, 2020)
The multiple sclerosis therapeutic teriflunomide is known to block the de novo synthesis of pyrimidine in mitochondria by inhibiting the enzyme dihydroorotate-dehydrogenase (DHODH). The metabolic processes of oxidative phosphorylation and glycolysis are further possible downstream targets. In healthy adult mice, high levels of dihydroorotate-dehydrogenase (DHODH) activity are measured in the central nervous system (CNS), and DHODH inhibition may cause indirect effects on reactive oxygen species production and NADPH oxidase (NOX) mediated oxidative stress, known to be key aspects of the inflammatory response of the CNS. However, little is known about the effect of teriflunomide on the dynamics of NOX activation in CNS cells and subsequent alterations of neuronal function in vivo. In this study, we employed fluorescence lifetime imaging (FLIM) and phasor analysis of the endogeneous fluorescence of NAD(P)H (nicotinamide adenine dinucleotide phosphate) in the brain stem of mice to visualize the effect of teriflunomide on cellular metabolism. Furthermore, we simultaneously studied neuronal Ca2+ signals in transgenic mice with a FRET-based Troponin C Ca2+ sensor based (CerTN L15) quantified using FRET-FLIM. Hence, we directly correlated neuronal (dys-)function indicated by steadily elevated calcium levels with metabolic activity in neurons and surrounding CNS tissue. Employing our intravital co-registered imaging approach, we could not detect any significant alteration of NOX activation after incubation of the tissue with teriflunomide. Furthermore, we could not detect any changes of the inflammatory induced neuronal dysfunction due to local treatment with teriflunomide. Concerning drug safety, we can confirm that teriflunomide has no metabolic effects on neuronal function in the CNS tissue during neuroinflammation at concentrations expected in orally treated patients. The combined endogenous FLIM and calcium imaging approach developed by us and employed here uniquely meets the need to monitor cellular metabolism as a basic mechanism of tissue functions in vivo.